2022
DOI: 10.1111/tpj.15686
|View full text |Cite
|
Sign up to set email alerts
|

Direct regulation of shikimate, early phenylpropanoid, and stilbenoid pathways by Subgroup 2 R2R3‐MYBs in grapevine

Abstract: The stilbenoid pathway is responsible for the production of resveratrol in grapevine (Vitis vinifera L.). A few transcription factors (TFs) have been identified as regulators of this pathway but the extent of this control has not been deeply studied. Here we show how DNA affinity purification sequencing (DAP-Seq) allows for the genome-wide TF-binding site interrogation in grape. We obtained 5190 and 4443 binding events assigned to 4041 and 3626 genes for MYB14 and MYB15, respectively (approximately 40% of peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 71 publications
4
41
0
Order By: Relevance
“…The second use case aims to characterize a grapevine gene family and identify those members that show tissue-specific expression and modulation upon biotic stresses. The last use case explores a high number of target genes modulated by the MYB14 transcription factor obtained in Orduña et al (2022) . This set of MYB14-bound genes was filtered according to the TF-binding position in: (i) upstream-bound (up to −3 kb from each transcription start site) and (ii) gene body and downstream-bound (coding sequence and untranslated regions, up to 2 kb from the end of each gene feature).…”
Section: Resultsmentioning
confidence: 99%
“…The second use case aims to characterize a grapevine gene family and identify those members that show tissue-specific expression and modulation upon biotic stresses. The last use case explores a high number of target genes modulated by the MYB14 transcription factor obtained in Orduña et al (2022) . This set of MYB14-bound genes was filtered according to the TF-binding position in: (i) upstream-bound (up to −3 kb from each transcription start site) and (ii) gene body and downstream-bound (coding sequence and untranslated regions, up to 2 kb from the end of each gene feature).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the cistrome in the promoter sequences of these genes shown that they are potential targets of the transcription factors MYB13, MYB14 and MYB15. The control of STS and other biosynthetic genes of the shikimate pathway is now a known case (Höll et al , 2013;Wong et al , 2016;Vannozzi et al , 2018;Orduña et al , 2022). More intriguing is the apparent involvement of the aforementioned TFs in the regulation of gene clusters linked to the biosynthesis of terpenes and other flavonoids, as well as their involvement in the regulation of genes that show divergent expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis highlighted thecis element GGTAGGTG (P-val 5.4E-14, FDR 9.1E-12) as the best ranked enriched motif. This element, in addition to representing a target of the TF VvMYB03 based on PlantDBTF, was found to be the binding site of VvMYB13, VvMYB14 and VvMYB15 based on a recent study in which the cistroma of these TFs was studied through a DNA Affinity Purification Assay (DAPseq) (Orduña et al , 2022). To shed light on the regulation of these soil-responsive genes we therefore screened the DAPseq data to verify how many of the 740 genes were effective targets of MYB13-15.…”
Section: Influence Of Soil Variable On Transcriptional Variation In T...mentioning
confidence: 99%
“…(2021) . The use of metabolomics (stilbenoid-oriented) and transcriptomics, coupled to the genome-wide exploration of transcription factor binding sites through DAP-seq, allowed Orduña et al. (2022) to identify new candidate genes coding for resveratrol modifying enzymes including laccasses, glycosyltransferases and O -methyl-transferases, potentially producing viniferin, piceid and pterostilbene, respectively.…”
Section: Multi-omics Integration Of Transcriptomics and Metabolomicsmentioning
confidence: 99%